Delivering performance in food supply chains - Mena, Carlos; Stevens, Graham (Woodhead Publishing in food science, technology, and nutrition, 2010)
Food and drink supply chains are complex, continually changing systems, involving many participants. They present stakeholders across the food and drinks industries with considerable challenges. Delivering performance in food supply chains offers expert perspectives to help practitioners and academics to improve their supply chain operations. The Editors have identified six key challenges in managing food and drinks supply chains. Each section of the book focuses on one of these important issues. The first chapters consider the fundamental role of relationship management in supply chains. The next section discusses another significant issue: aligning supply and demand. Part three considers five different approaches to effective and efficient process management, while quality and safety management, an issue food companies need to take very seriously, is subject of the next section. Parts five and six review issues which are currently driving change in food supply chains: the effective use of new technologies and the desire to deliver food sustainably and responsibly. With expert contributions from leaders in their fields, Delivering performance in food supply chains will help practitioners and academics to understand different approaches in supply chain management, explore alternative methods and develop more effective systems. Considers the fundamental role of relationship management in supply chains including an overview of performance measurement in the management of food supply chainsDiscusses the alignment of supply and demand in food supply chains and reviews sales and operations planning and marketing strategies for competitive advantage in the food industryProvides an overview of the effective use of new technologies and those that will be used in the future to deliver food sustainably and reliably.